OPPORTUNITIES AND CHALLENGES OF THE ONLINE LEARNING IN WEST SUMATERA: WHAT STUDENTS SAY ABOUT IT? - Dina Ramadhanti; Diyan Permata Yanda (Universitas Negeri Makassar, 2023)
This research is a survey research to find out the opportunities and challenges of online learning in West Sumatra. A total of 227 students were randomly selected from two universities in West Sumatra as research participants. By conducting in-depth interviews, information was obtained about students' views on online learning in West Sumatra. An unstable internet network is a major problem for students to take online learning. Online learning opportunities in West Sumatra, namely: online learning provides benefits because it is more flexible and can be followed anywhere and anytime, students can carry out learning while entrepreneurship or work, and various educational institutions in West Sumatra with their quality have the potential to be able to keep up with the times by carrying out online learning in a more planned and programmed way. The challenges of implementing online learning in West Sumatra, namely: provincial and local governments need to provide internet services widely and reach all regions in West Sumatra, students need to be educated to be able to become independent learners from an early age, teachers need to design accessible learning content by students and must be by the needs of students, and the government needs to make efforts to provide extensive library services that can be accessed online.